REIMAGINING THE DIGITAL ORACLE: AN AFRICAN PHILOSOPHICAL AND THEOLOGICAL CRITIQUE OF ARTIFICIAL INTELLIGENCE - Bukola Abosede Folaranmi; Moses Adeolu Agoi; Zohaib Hassan Sain; Shazadi Hina Sain; Aulia Luqman Aziz (Srawung: Journal of Social Sciences and Humanities, 2025)
The emergence of artificial intelligence (AI) as a source of insight invites its characterization as a "digital oracle," a metaphor with particular resonance in Africa where traditions of divination are deeply embedded. This analogy, however, raises critical questions regarding the understanding, legitimacy, and governance of such systems. This paper employs a multidisciplinary approach, integrating contemporary AI ethics with African philosophy and religious perspectives, to analyze this metaphor. Using the prophetic figure central to Yoruba Ifá divination as a comparative framework, we contrast the communal, symbolically interpreted guidance of traditional oracles (Bascom, 1969) with AI's data-driven predictions, which often lack moral authority and community accountability. In response, we propose that the Ubuntu philosophy, grounded in relational humanity and moral duty, provides a vital corrective. The analysis is structured around four lenses: (1) epistemic opacity and interpretive authority; (2) relational personhood and communal responsibility; (3) spiritual and moral discernment; and (4) decolonial governance. We argue that AI should not be considered an autonomous philosophical oracle but can serve as a valuable decision-support tool when consciously embedded within robust systems of ethics, interpretation, and community. The paper concludes by advocating for AI development guided by Ubuntu ethics, the inclusion of religious thought, and formal decolonial governance. This approach seeks to transform AI into a context-aware tool that serves humanity, rather than an unaccountable digital predictor.